The Integrated Model of Dwyer and Kim as a Tool to Evaluate and Rank the Determinant Attributes of a Tourist Destination Competitiveness - Berdo, Sonila (European Journal of Economics and Business Studies, 2015)
The aim of this paper is to explain the importance of the Integrated model of Dwyer - Kim, in terms of its application to different tourist destinations, as a valuable tool to measure and evaluate the impact of different factors in their competiveness level and making possible to compare them to each other. Managing tourist destination competitiveness is a very challenging process. This model serves as a tool to identify, to evaluate and rank the importance of different attributes and sub-attributes of a tourist destination. Having the information on the relative importance of all the factors and sub-factors makes destinations/countries well oriented to select and invest or effectively manage those factors which are of high impact in achieving and maintaining the sustainable competitiveness level in the market. How this model is composed? Which factors and sub-factors are involved in this model for being evaluated and ranked, as tourist destination competitiveness attributes? How these factors and sub-factors can be converted in measurable ones? How this model can be applied in practice? Answering the above questions and giving some evidences in different countries about the last question will be the objectives of this paper. After a literature review process on different models of evaluating tourist destination competitiveness, the integrated model of Dwyer - Kim, here presented, results as the most completed model which does integrate the both sides of the tourist market factors, those of the supply and demand side.